Effectiveness of the SIJAKAWANGI and SIPUNDIWANGI Programs on Taxpayer Compliance - Adelia Mustika Nanda; Arum Syifa Mutiara Hati; Hesty Rizqi Aulannida; Vinchen Jezzica Arifin (Majapahit Journal of Islamic Finance and Management, 2026)
Low taxpayer compliance in the local tax sector remains a serious concern that requires concrete solutions to encourage greater public awareness in fulfilling tax obligations. This study aims to describe the effectiveness of SIJAKAWANGI (Banyuwangi Regency Regional Tax Information System) and SIPUNDIWANGI (Banyuwangi Regional Tax Draw Implementation System) in improving taxpayer compliance in Banyuwangi Regency. This study uses a qualitative research method with a descriptive approach, enabling the researcher to describe the phenomenon comprehensively based on actual field conditions. Data were gathered through triangulation encompassing in-depth interviews, observation, and documentation. Three informants were selected using a purposive technique, whereby informants were deliberately chosen based on their relevance to the research focus, independent of statistical logic or population representation. The informants consisted of a tax mapper operator, a taxpayer, and a BAPENDA employee responsible for managing both programs. Data analysis was conducted in three stages: data reduction, data presentation, and conclusion drawing. The findings reveal that SIJAKAWANGI automatically records every transaction in real-time, encouraging taxpayers to report their obligations more honestly and transparently. Meanwhile, SIPUNDIWANGI serves as a complementary program that motivates the public through a prize draw mechanism, resulting in greater enthusiasm and active participation in fulfilling tax obligations. The implementation of both programs together has proven capable of creating a more orderly, transparent, and conducive tax ecosystem in Banyuwangi Regency.